ПРИНЦИПЛЕРДИ ӘМЕЛГЕ АСЫРЫЎ ТИЙКАРЫНДА СТУДЕНТЛЕРГЕ МӘДЕНИЯТЛАРАРАЛЫҚ БАЙЛАНЫСТЫ ҮЙРЕТИЎ СИСТЕМАСЫ - Менлимуратова, Э.А. (FAN va JAMIYAT, 2021)
The article discusses the issue of the system of teaching intercultural communication of students, which is based on the implementation of the principles. The proposed principles will contribute to the formation of intercultural relations among students and the achievement of practical and developmental goals provided for in the target standards of higher education institutions. Teaching English should be based on respect, understanding and acceptance of cultural differences between the home country and the country of the target language.